Perspektif Hukum Normatif terhadap Pelindungan Data Genetik dalam UU PDP 2022 - Alezra Pramesti Bonde; Shilvy Anggraini; Sidi Ahyar Wiraguna; Andika Nugraha Santoso; Ruth Elleny (Jurnal Hukum Lex Generalis, 2026)
The rapid development of genomic technology and the digitalization of healthcare systems have significantly increased the collection, storage and processing of genetic data across medical services, biomedical research, pharmaceutical industries and artificial intelligence-based health technologies. Genetic data possess distinctive characteristics compared to ordinary personal data because they are unique, permanent, immutable and biologically linked to family members. These characteristics place genetic data among the most sensitive categories of personal information and necessitate enhanced legal protection. Indonesia, through Law Number 27 of 2022 concerning Personal Data Protection, recognizes genetic data as a category of specific personal data. Nevertheless, the current regulatory framework remains general in nature and does not specifically regulate the processing, storage, utilization, cross-border transfer and deletion of genetic information. This study aims to analyze the legal protection of genetic data under the Indonesian Personal Data Protection Law and compare it with regulatory frameworks established under the European Union General Data Protection Regulation (GDPR), Singapore’s Personal Data Protection Act (PDPA) and South Korea’s Personal Information Protection Act (PIPA). This research employs normative legal research methods using statutory, conceptual and comparative approaches. The findings indicate that although the recognition of genetic data as specific personal data constitutes a significant advancement in Indonesian law, the existing framework lacks sector-specific safeguards comparable to those found in the European Union, Singapore and South Korea. The absence of detailed regulations may create legal uncertainty, facilitate genetic discrimination, enable misuse of health information and undermine individual privacy rights. Therefore, Indonesia requires more comprehensive implementing regulations and specialized oversight mechanisms to ensure adequate protection of genetic data within the evolving digital health ecosystem.